2014
DOI: 10.1017/s1368980014000974
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of food sources to the vitamin B12 status of South Indian children from a birth cohort recruited in the city of Mysore

Abstract: Objective: There is evidence that subclinical vitamin B 12 (B 12 ) deficiency is common in India. Vegetarianism is prevalent and therefore meat consumption is low. Our objective was to explore the contribution of B 12 -source foods and maternal B 12 status during pregnancy to plasma B 12 concentrations. Design: Maternal plasma B 12 concentrations were measured during pregnancy. Children's dietary intakes and plasma B 12 concentrations were measured at age 9·5 years; B 12 and total energy intakes were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Page 1247 positive association between B12 levels and their children sampled at 9.5 years of age 16. Similar findings were reported by Yusufji et al, from Vellore 17.…”
supporting
confidence: 79%
“…Page 1247 positive association between B12 levels and their children sampled at 9.5 years of age 16. Similar findings were reported by Yusufji et al, from Vellore 17.…”
supporting
confidence: 79%
“…There is a dearth of large-scale global studies (especially in Indian adolescents) regarding the relationship between serum B12 concentration with area of residence, anthropometric indices and dietary vitamin B12 intake (17)(18)(19) . In the present study, we hypothesise that serum vitamin B 12 concentration in Indian school-going adolescents belonging to rural and urban households might be governed by their respective nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…This study also studied individual animal food groups, and fully adjusted differences in plasma vitamin B12 for low vs. high consumers were significant only for meat, but not for dairy, fish, cows liver, and eggs (32). In line with these findings, a study conducted in India ( n = 512) also showed statistically significant positive associations of the meat and fish group with plasma vitamin B12 in fully adjusted models, but not for other animal products (34). Others observed inverse associations between vitamin B12 intake from milk with plasma Hcy, but not for vitamin B12 intake from red meat or cheese (35).…”
Section: The Association Of Animal Food Products Containing Vitamin Bmentioning
confidence: 55%
“…When considering different animal products within individual studies among children, differences in vitamin B12 concentrations were most pronounced when comparing high vs. low intake of dairy products, followed by meat and fish intake (32), and dairy products showed stronger correlations with vitamin B12 and holoTC concentrations compared to liver pate, meat and fish (33). In another study, only a combined group of meat and fish was associated with vitamin B12 concentrations, whereas the individual components fish, chicken, eggs, and dairy were not related to plasma vitamin B12 (34).…”
Section: The Association Of Animal Food Products Containing Vitamin Bmentioning
confidence: 99%
See 1 more Smart Citation